Deadly pathogens, transformative technologies, and protracted pandemics: challenges and opportunities in laboratory medicine - Pritt, Bobbi S.; Wang, Ping; Nuzzo, Jennifer; Zimmermann, Stefan; Burnham, Carey-Ann D (Clinical chemistry, 2022)
These are unprecedented times in medicine, and laboratory medicine is at the forefront. While advances in genomics and proteomics have dramatically improved our ability to diagnose and characterize infectious diseases, the world faces momentous challenges from increasing antimicrobial resistance, resurgence of ancient scourges, and outbreaks of emerging pathogens. There have been more than a dozen viral diseases outbreaks in the past 2 decades alone (Fig. 1), and the emergence of novel viral pathogens is predicted to accelerate in coming years (1). Most notable is the coronavirus disease 2019 (COVID-19) outbreak, which continues to upend daily lives around the planet and raise many medical, social, economic, and political issues. This special issue of Clinical Chemistry highlights the major challenges faced by the global laboratory medicine community, as well as the opportunities provided by the development and implementation of transformative technologies.
Published: 30 December 2021
Gesehen am 08.04.2022